The Boundedness of Marcinkiewicz Integrals on Grand Variable Herz Spaces (Analysis in Theory and Applications, 2023)
Under some natural regularity assumptions on the exponent function, we obtain the boundedness of Marcinkiewicz integrals $μ,$ $μ^ρ_S$ and $μ^{∗,ρ}_λ$ on grand variable Herz spaces. Our results enrich and improve some previous results in the literature.